Kepuasan Dan Loyalitas Konsumen Air Minum Isi Ulang Di Kota Padang - Awisal Fasyni; Mukhamad Najib; Kirbrandoko Kirbrandoko (Universitas Negeri Padang, 2020)
The increase in the number of refill drinking water consumption (AMIU) which is the main drinking water source for the people of Padang encourages the development of the AMIU industry. This has resulted in competition between drinking water depots (DAMIU) becoming increasingly stringent so that strategies need to be identified to win the competition. The purposes of this study were to identify the prioritized attributes by consumers in buying refill drinking water, analyzing customer satisfaction and loyalty as well as recommending measures for refill drinking water depot to win the competition. The research was conducted by using a survey of consumers of family and nonfamily. Prioritized attributes by consumers based on eckenrode method were water clarity, price, distance, source of raw water, water taste and odor of water. Consumers were classified as very satisfied based on CSI results. Based on IPA results, price performance, bonuses and workers hospitality were need to be improved. CLI results ​​indicate that consumers were loyal and there was a significant relationship between satisfaction and loyalty based on PLS. Recommendations for refill drinking water depot was to provide the best performance of prioritized attributes and increase customer satisfaction and loyalty.